Lung ultrasound-guided treatment for heart failure: An updated meta-analysis and trial sequential analysis - Li, Yan; Ai, Hu; Ma, Na; Li, Peng; Ren, Junhong (Frontiers in Cardiovascular Medicine, 2022)
Background: The usefulness of lung ultrasound (LUS) in guiding heart failure (HF) treatment is still controversial. Purpose: We aimed to evaluate the usefulness of LUS-guided treatment versus usual care in reducing the major adverse cardiac event (MACE) rate in HF patients. Methods: We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) identified through systematic searches of MEDLINE, EMBASE, the Cochrane Database, Google Scholar, and SinoMed. The primary outcome was MACEs (a composite of all-cause mortality, HF-related rehospitalization, and symptomatic HF). The required information size was calculated by trial sequential analysis (TSA). Results: Ten RCTs involving 1,203 patients were included. Overall, after a mean follow-up period of 4.7 months, LUS-guided treatment was associated with a significantly lower risk of MACEs than usual care (relative risk [RR], 0.59; 95% confidence interval [CI], 0.48–0.71). Moreover, the rate of HF-related rehospitalization (RR, 0.63; 95% CI, 0.40–0.99) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentration (standardized mean difference, −2.28; 95% CI, −4.34 to −0.22) were markedly lower in the LUS-guided treatment group. The meta-regression analysis showed a significant correlation between MACEs and the change in B-line count (P < 0.05). The subgroup analysis revealed that the risk of MACEs was markedly lower in patients aged up to 70 years (RR, 0.54; 95% CI, 0.44–0.67), with a lower rate of atrial fibrillation (<27.2%) (RR, 0.53; 95% CI, 0.43–0.67), and with a lower NT-proBNP concentration (<3433 pg/mL) (RR, 0.51; 95% CI, 0.40–0.64). TSA indicated a lower risk of MACEs with LUS-guided treatment than with usual care among HF patients (P < 0.05). Conclusions: LUS seems to be a safe and effective method to guide HF treatment.